(untitled) (Tempo e Argumento, 2022)
The analytical perspective of global history provides keys and pertinent aspects for thinking about the connections between people, projects, political groups and ideas. The aim of this article is to analyze, from the perspective of global history, the transnational solidarities that turned to Brazilian women or which they integrated during the exile of the Brazilian military dictatorship in France and Portugal. It seeks to demonstrate the connections between Brazilian and French women and between Brazilian and Portuguese women. Global history will help to compress the transnational solidarities and feminist or female solidarities that existed in the period, from the slogan of the time: sisterhood is global. The timeline is from 1973 (the year of the military coup in Chile, which took many Latin American women to Europe) until 1979 (when Amnesty Law nº 6.683 was issued). The main sources are the documents of the Círculo de Mulheres Brasileiras em Paris, and of the Movimento Democrático de Mulheres in Portugal, and the Nosotras newspapers of the Latin American Women’s Group in Paris. In addition, in order to complement some information, reports from the Abroad Information Bureau (CIEx) and three interviews with major exiled women were used. Keywords: exiled women; transnational solidarities; global perspective.